Innovative circular bioeconomy and decarbonization approaches in palm oil waste management: A review - Goh, Kai Chen; Kurniawan, Tonni Agustiono; AlSultan, G. Abdulkareem; Othman, Mohd Hafiz Dzarfan; Anouzla, Abdelkader; Aziz, Faissal; Ali, Imran; C. Casila, Joan Cecilia; Khan, Muhammad Imran; Zhang, Dongdong; Onn, Choo Wou; Seow, Ta Wee; et al. (elsevier, 2025)
The palm oil sector is a major contributor to global waste and greenhouse gas (GHG) emissions, posing significant challenges for sustainability. This study explores innovative circular bioeconomy and decarbonization strategies in palm oil waste management, with a focus on reducing environmental impact and improving resource efficiency within the industry. This work also evaluates the potential of waste-to-energy technologies, such as anaerobic digestion and biomass combustion, to reduce carbon emissions and generate renewable energy from palm oil mill by-products. Key findings reveal that integrating circular bioeconomy practices, including the reuse of waste for bioproducts and biofuels, can decrease GHG emissions by up to 30 % and significantly reduce waste disposal costs. Transitioning to biogas and solar energy could reduce the carbon footprint by 40–50 %, while adopting carbon capture and storage (CCS) could capture 90 % of CO₂ emissions, equivalent to 1.2 million tons annually. Enhanced reforestation projects could sequester up to 1.1 billion tons of CO₂ and improved palm oil mill effluent (POME) management could cut CH4 emissions by 70 %. Additionally, bioenergy production from palm biomass significantly lowers operational emissions, contributing to a 35 % reduction in the industry’s GHG output. The adoption of sustainable certifications like RSPO has reduced deforestation by 15 %. Furthermore, the study identifies key technological and economic barriers to widespread adoption, such as high initial capital investment and limited infrastructure. Policy interventions, such as carbon pricing and subsidies for green technologies, are recommended to accelerate the implementation of these strategies. The findings highlight the potential of circular bioeconomy and decarbonization approaches to transform palm oil waste management into a more sustainable and resource-efficient process, contributing to both environmental and economic benefits. This research provides actionable policy recommendations to promote sustainability and achieve carbon